Alat Pengukur Getaran Berbasis Mikrokontroller Atmega 16 Menggunakan Sensor Microphone - Munandar, Mahmud Ari, Dr. Ratnasari Nur Rohmah, ST, MT, Dedi Ari Prasetya,ST (2015)
Vibration is a back and forth motion around equilibrium. The equilibrium point is a state where an object is at rest if no force acting on the object. Vibration having amplitude (deviation farthest distance with the midpoint) of the same. An electric machine which can be produced the vibration, the use of the electric machine for a long time can lead to vibration effects berbada at the time of the engine in its normal condition. Vibration measurements on electrical machine can be made directly and indirectly (convert sound). Engine vibration measuring device uses a sensor microphone is based ATMega 16 merupkan vibration gauges indirectly. This tool converts the audio signal (sound) into electrical signals. Microcontroller as an analog signal converter into a digital thereof in the form of data and 16x2 character LCD as its output in the form of a value (number). From the test results based microcontroller vibration measuring device ATMega 16 using sensor microphone microphone sensor measurement results obtained by measuring the distance of less than 5 cm at 1700 rpm rotational speed measurement result measured by a device made of 323Hz and 66 dB at the microphone sensor readings A. While the sensor measurement microphone B scalable 512Hz and 68 dB. Measurements with conventional measuring instruments with an oscilloscope and a decibel meter measurements obtained at 453 Hz at the output of the sensor microphone A and 624 Hz is in coupling with an oscilloscope. While the measurement noise measured by a decibel meter measurement results obtained 68.9 dB. To measure the rotational speed 1700 rpm with a distance of more than 5 cm measurement obtained on the measurement results measured by a device made of 422Hz and 66 dB at the microphone sensor readings A. While the sensor measurement microphone and measured 528 Hz and 68 dB. Measurements with conventional measuring instruments with an oscilloscope and a decibel meter measurements obtained at 453 Hz at the output of the sensor microphone A and 624 Hz is in coupling with an oscilloscope. While the measurement noise measured by a decibel meter measurement results obtained 78.4 dB. Vibration measurements by using a sensor microphone that the closer the distance measurement and high motor speed the greater the error value is read by the tool, because the closer the object, the sensor readings with the greater noise generated as well.   Keywords: dB, vibration, LCD, and sensor mikrontroller microphone.